Deposition of Titanium Aluminium Nitride Thin Layer on High Speed Steel Substrate by Radio Frequency Sputtering - Sigit Tri Wicaksono; I G.N.B. Dwistha Prayukti; Agung Purniawan; Tri Mardji Atmono (IPTEK Journal of Proceedings Series, 2017)
High Speed Steel (HSS) has been widely used in manufacturing industry as one of cutting tool materials because of its good mechanical properties yet with a low price. However, since this material has a low thermal resistance property, it will limit its application when used in dry cutting process. Several methods have been used to improve the cutting performance of HSS in dry cutting. One of them was by growing a thin layer of hard coating on the contact surface of the cutting tool material. In this research, Titanium Aluminium Nitride layer were deposited on AISI M41 High Speed Steel substrate by using Radio Frequency (RF) Sputtering method. The aims of this study were to analyze the effect of variations of Aluminium surface area ratios (10, 20, 30, and 40 %) on the Titanium target and also to analyze the effect of deposition time (15, 30, and 45 minutes) on the composition, phase characterization and morphology of the thin layer that formed. The formation of TiAlN and AlN crystalline compounds were observed by X-Ray Diffraction method. A dense layer with a thickness range from 1.4 to 5.2 µm was observed by using a Scanning Electron Microscopy. It was known that the deposition time affect the thickness and also the roughness of the layer. The topography images by Atomic Force Microscopy showed that the deposition time of 45 minutes produce the finest layer with the surface roughness of 10.8 nm.